2017
DOI: 10.1597/15-088
|View full text |Cite
|
Sign up to set email alerts
|

Children's Attitudes toward Peers with Unintelligible Speech Associated with Cleft Lip and/or Palate

Abstract: Typically developing children tended to make negative social and personal attribute judgments about children with cleft palate based solely on the intelligibility of their speech. Society, educators, and health professionals should work together to ensure that children with cleft palate are not stigmatized by their peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…A listeners attitudes and judgments about a person's age, health, social and educational status are often based on the person's speech characteristics (Allard & Williams, 2008). Negative stereotyping, due to communication disorders, is of high importance to society, since it may cause psychological, educational, and employment disadvantages (Lee et al, 2016). Also in children negative attitudes toward peers with speech impairments have been observed and subjective perceptions of speech have been related to social acceptance (Blood & Hyman, 1977;Watterson et al, 2013).…”
Section: Perception Of Speechmentioning
confidence: 99%
“…A listeners attitudes and judgments about a person's age, health, social and educational status are often based on the person's speech characteristics (Allard & Williams, 2008). Negative stereotyping, due to communication disorders, is of high importance to society, since it may cause psychological, educational, and employment disadvantages (Lee et al, 2016). Also in children negative attitudes toward peers with speech impairments have been observed and subjective perceptions of speech have been related to social acceptance (Blood & Hyman, 1977;Watterson et al, 2013).…”
Section: Perception Of Speechmentioning
confidence: 99%
“…Witt et al (1997) concluded that peer group evaluations of cleft palate speech are more relevant to the patients themselves. Lee et al (2017) stated that there is an apparent gap in our knowledge about children's attitudes to their peers with cleft palate speech. They investigated typically developing children's attitudes to speech samples of children born with cleft palate with varying speech intelligibility.…”
mentioning
confidence: 99%
“…Good intelligibility is crucial for speech function and social interaction in everyday life (Lee et al, 2016). Therefore, a valid measure of intelligibility is of great importance when evaluating CP care.…”
mentioning
confidence: 99%